Autosomal dominant tubulointerstitial kidney disease-UMOD is the most frequent non polycystic genetic kidney disease - Gast, Christine; Marinaki, Anthony; Arenas-Hernandez, Monica; Campbell, Sara; Seaby, Eleanor G; Pengelly, Reuben J; Gale, Daniel P; Connor, Thomas M; Bunyan, David J; Hodaňová, Kateřina; Živná, Martina; Kmoch, Stanislav; et al. (BMC nephrology, 2018)
BACKGROUND: Autosomal dominant tubulointerstitial kidney disease (ADTKD) caused by mutations in the UMOD gene (ADTKD-UMOD) is considered rare and often remains unrecognised. We aimed to establish the prevalence of genetic kidney diseases, ADTKD and ADTKD-UMOD in adult chronic kidney disease (CKD) patients, and to investigate characteristic features. METHODS: We sent questionnaires on family history to all patients with CKD stages 3-5 in our tertiary renal centre to identify patients with inherited renal disease. Details on clinical and family history were obtained from patient interviews and clinical records. Sanger sequencing of the UMOD gene was performed from blood or saliva samples. RESULTS: 2027 of 3770 sent questionnaires were returned. 459 patients reported a family history, which was consistent with inherited kidney disease in 217 patients. 182 non-responders with inherited kidney diseases were identified through a database search. Of these 399 individuals, 252 had autosomal dominant polycystic kidney disease (ADPKD), 28 had ADTKD, 25 had Alports, and 44 were unknown, resulting in 11% of CKD 3-5 patients and 19% of end-stage renal disease patients with genetic kidney diseases. Of the unknown, 40 were genotyped, of whom 31 had findings consistent with ADTKD. 30% of unknowns and 39% of unknowns with ADTKD had UMOD mutations. Altogether, 35 individuals from 18 families were found to have ten distinct UMOD mutations (three novel), making up 1% of patients with CKD 3-5, 2% of patients with end-stage renal disease, 9% of inherited kidney diseases and 56% with ADTKD. ADTKD-UMOD was the most common genetic kidney disease after ADPKD with a population prevalence of 9 per million. Less proteinuria and haematuria, but not hyperuricaemia or gout were predictive of ADTKD-UMOD. The main limitations of the study are the single-centre design and a predominantly Caucasian population. CONCLUSIONS: The prevalence of genetic kidney diseases and ADTKD-UMOD is significantly higher than previously described. Clinical features poorly predicted ADTKD-UMOD, highlighting the need for genetic testing guided by family history alone.
Keywords: senioři; genetické testování; uromodulin; Prevalence; polycystické ledviny autozomálně dominantní; intersticiální nefritida; UMOD; Renal Insufficiency, Chronic; chronická renální insuficience; Middle Aged; průzkumy a dotazníky; mužské pohlaví; Nephritis, Interstitial; ženské pohlaví; Humans; Surveys and Questionnaires; lidé středního věku; Polycystic Kidney, Autosomal Dominant; Uromodulin; Genetic kidney disease; Genetic Testing; Female; Aged; lidé; Male; Autosomal dominant tubulointerstitial kidney disease